2011
DOI: 10.1001/archneurol.2010.346
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the Association Between Variants in SORL1 and Alzheimer Disease

Abstract: Objective-To reexamine the association between the neuronal sortilin-related receptor gene (SORL1) and Alzheimer disease (AD).Design-Comprehensive and unbiased meta-analysis of all published and unpublished data from case-control studies for the SORL1 single-nucleotide polymorphisms (SNPs) that had been repeatedly assessed across studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
116
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 153 publications
(132 citation statements)
references
References 37 publications
14
116
1
1
Order By: Relevance
“…5 SORL1 has already been the subject of numerous association studies focused on frequent polymorphisms (for a complete overview, see Alzgene, www.alzgene.org), yielding mixed results, although a recent meta-analysis, including more than 12 000 cases and 17 000 controls, concluded that multiple SORL1 alleles in distinct linkage disequilibrium blocks are associated with AD risk. 6 We also determined the allele frequency of each variant in a cohort of 1500 control individuals matched for ethnic origin. This work confirmed that all variants were indeed private variants not found in controls.…”
Section: Resultsmentioning
confidence: 99%
“…5 SORL1 has already been the subject of numerous association studies focused on frequent polymorphisms (for a complete overview, see Alzgene, www.alzgene.org), yielding mixed results, although a recent meta-analysis, including more than 12 000 cases and 17 000 controls, concluded that multiple SORL1 alleles in distinct linkage disequilibrium blocks are associated with AD risk. 6 We also determined the allele frequency of each variant in a cohort of 1500 control individuals matched for ethnic origin. This work confirmed that all variants were indeed private variants not found in controls.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, there is strong support for the involvement of SORLA in sporadic AD, which stems from population-based studies that document association of genetic variants of SORL1 (the gene encoding SORLA) with sporadic AD in several ethnicities (Rogaeva et al, 2007;Bettens et al, 2008;Cuenco et al, 2008;Lee et al, 2008;Webster et al, 2008). Cumulative meta-analyses encompassing in excess of 30,000 individuals (Reitz et al, 2011) and genomewide association studies Naj et al, 2011) confirm the association of single nucleotide polymorphisms (SNPs) in SORL1 with AD.…”
Section: Sorla a Neuronal Trafficking Receptor Implicated In Admentioning
confidence: 99%
“…One half of the genetic variance is attributable to mutations in APP, PSEN1, PSEN2, and the APOE e4-allele, and they have been shown to cause the overproduction or reduced clearance of Ab (Rogaeva et al 2006). More recently, it was demonstrated that single nucleotide polymorphisms (SNP) in SORL1 are significantly associated with late-onset AD in several independent cohorts (Rogaeva et al 2007;Reitz et al 2011). In addition,…”
mentioning
confidence: 99%